2018
DOI: 10.1021/jacs.8b08610
|View full text |Cite
|
Sign up to set email alerts
|

Subtle Changes in Lipid Environment Have Profound Effects on Membrane Oxidation Chemistry

Abstract: Nature carefully designs the components of amphiphile-composed monolayer and bilayer membranes to deliver specific functions. The compositions of these interfacial layered structures are so delicate that minute modifications can result in huge changes in function. Great efforts have been expended to understand membrane physical properties, with only minimum attention given to associated chemical properties. Here we report the first examples of the delicate chemistry associated with membrane amphiphilic compone… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

2
61
0

Year Published

2019
2019
2020
2020

Publication Types

Select...
6

Relationship

6
0

Authors

Journals

citations
Cited by 34 publications
(63 citation statements)
references
References 37 publications
2
61
0
Order By: Relevance
“…Apparently the host–guest interaction between G and OA exhibits an excellent antioxidation ability. In our previous studies on the effect of packing density on oxidation chemistry at the air–water interface, many examples revealed that the permeability of an oxidizer into the monolayer is significantly lowered as a result of dense packing . Therefore, we postulate that the tight binding between OA and G, and the ionic attraction between protonated G molecules via Cl − bridges and hydrogen bonds with water make a compactly packed monolayer, which consequently lowers the permeability of OH, quenching the oxidation reactions.…”
Section: Figurementioning
confidence: 86%
See 1 more Smart Citation
“…Apparently the host–guest interaction between G and OA exhibits an excellent antioxidation ability. In our previous studies on the effect of packing density on oxidation chemistry at the air–water interface, many examples revealed that the permeability of an oxidizer into the monolayer is significantly lowered as a result of dense packing . Therefore, we postulate that the tight binding between OA and G, and the ionic attraction between protonated G molecules via Cl − bridges and hydrogen bonds with water make a compactly packed monolayer, which consequently lowers the permeability of OH, quenching the oxidation reactions.…”
Section: Figurementioning
confidence: 86%
“…According to the well‐known mechanism of SDO reaction with olefins, the unsaturated chain of OA should be converted to allyl hydroperoxide functionality (‐OOH), which can further decompose to a hydroxyl group (‐OH) (mechanism provided in Figure S4). Due to the low packing intensity of the OA monolayer, SDO enjoys a less crowded environment so that it can diffuse more freely to engage in oxidation chemistry. Therefore, around 37 % of OA is oxidized into OAOOH − or OAOH − after 60 s of oxidation time.…”
Section: Figurementioning
confidence: 99%
“…In the current study, we adopt our unique home-built field-induced droplet ionization mass spectrometry (FIDI-MS) methodology (Figure 1), which is capable of selective online sampling of molecules that reside at the air-water interface and suffers minimal influence from the bulk of the solution. [27][28][29][30] Amphiphilic lipids, the major oxidation target of PDT, [1] and their oxidation products especially those unstable products that could easily degrade, can be detected by FIDI-MS in an in situ manner. The posterchild PS, 5,10,15,20-tetra(m-hydroxyphenyl)chlorin (temoporfin, T for short), is selected in this study for its high quantum yield and benign, tissue-penetrating activation wavelength (652 nm).…”
mentioning
confidence: 99%
“…In PDT,c ancer cells are attacked in different manners including direct killing of tumor cells by triggering apoptosis,v ascular damage,a nd the activation of an immune response. [1] TheFIDI-MS method [19][20][21][22][23] developed in our group has been proven to be interfacially sensitive,and it selectively samples molecules that are at the air-water interface after aw ell-defined reaction time.P revious FIDI-MS studies of interfacial chemistry have used hanging droplets. This is because the nascent products stemming from SO oxidation are themselves highly reactive,e asily degrading or evolving into other products over time or during sample characterization.…”
mentioning
confidence: 99%
“…[2][3][4][5][6] Although the general mechanisms of PDT targeting unsaturated phospholipids, [7][8][9][10][11] residues of proteins or peptides, [12] and nucleic acid components of DNAand RNA [13] are known, the details of reactions between PS-generated SO and substrate molecules at the molecular level remain elusive, [14] especially at the early stage of the reaction. [21][22][23] Acoustically levitated droplets promise to be "wall-less" airborne reactors with no interference resulting from contact with asupport, [24a] and sound is less invasive than other levitation techniques such as optic tweezers. [15] Frequently used characterization methods for lipid oxidation, such as oxygen consumption, fluorescence,a nd chromatographic measurements are either indirect or involve extensive sample handling and transfer.…”
mentioning
confidence: 99%